Kedah govt passing the buck to developers - Baharuddin, Noor Adzman (New Straits Times, 2012)
WITH the general election around the comer,no political party could afford to goof big time. A case in point is the Kedah Pakatan Rakyat government's plan to introduce a new housing policy.